The system of two miscible liquids as a generator of nanoparticles. The synthesis of BaSO4 nanoparticles upon contact of precursor solutions in water and tetrahydrofuran - E. A. Khristich; E. A. Mishchikhina; V. K. Khlebnikov; A. P. Kaplun; V. I. Popenko; Т. М. Buslaeva; L. I. Boguslavsky (Тонкие химические технологии, 2011)
The system of two miscible liquids is presented as a generator of nanoparticles. This approach was tested experimentally with the synthesis of barium sulfate nanoparticles under non-equilibrium conditions after contact of perfectly miscible solutions as an example.The experimental results were compared with the dynamic model of transition layer. According to this model the smallest size of obtained particles is determined by the size of associates in the nucleation stage formed inside the rotating Bernard cells. The hypothesis of BaSO4 creation is based on the idea that the interface between a Bernard cell and the surrounding solution has barrier properties. The permeability of this barrier depends on the viscosity of the solution. The influence of the solvent polarity on the structure and size of nanoparticles was investigated. The dependence of the structure and size of the nanoparticles on the water/THF ratio was found. The influence of viscosity of the solution on the size of the nanoparticles was found and explained in terms of dynamic transition layer.